Peningkatan Hasil Belajar Siswa MTs pada Materi Kesebangunan dan Kekongruenan Melalui Model Pembelajaran Kooperatif Tipe Jigsaw - Nordina Shaufia; Mayang Gadih Ranti (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2020)
Similarity and Congruences is a part of geometry which is considered by students as a difficult Topic. It was detected by a low result study and incompleteness of learning achievement clasiccaly. The using of Learning Copperative Model type Jigsaw is considered as an alternative to improve learning achievement of MTs Modern Puteri Cindai Alus Students because it can make student has a responsibility on their study and make an active discussion in Solving Problem. The research method is Action Research which consists of four steps, Planning, Action, Observation dan Reflection in two cycles. The research subjects are 20 students of Class IX MTs Modern Puteri Cindai Alus. The research results shows that there ia an improving of results study from middle to good category and leaning achivement classicaly improve from less to good category.